Eleven microsatellites in an emerging invader, Phytolacca americana (Phytolaccaceae), from its native and introduced ranges1. (9th March 2015) - Bentley, Kerin E.; Berryman, Kaelyn R.; Hopper, McGee; Hoffberg, Sandra L.; Myhre, Karin E.; Iwao, Keisuke; Lee, Jared B.; Glenn, Travis C.; Mauricio, Rodney
Abstract : Premise of the study: To facilitate population genetic analyses, microsatellite markers were developed for pokeweed ( Phytolacca americana ), a large, weedy, perennial herb native to eastern North America that is emerging as a significant invasive species in China. Methods and Results: We mined 1, 100, 538 Illumina MiSeq reads from genomic DNA for microsatellites and identified 58 primer pairs. We screened these primers for polymorphism in two native and two invasive populations. We identified 11 loci that amplified consistently. The number of alleles per locus ranged from two to six, and observed heterozygosity ranged from 0.00 to 1.00. All loci were largely monomorphic within populations but different among populations. The primers were of very limited use in the congener P. acinosa . Conclusions: These loci will provide a valuable resource to study the population genetics and invasion history of P. americana .